Lentilactobacillus hilgardii Inoculum, Dry Matter Contents at Harvest and Length of Conservation Affect Fermentation Characteristics and Aerobic Stability of Corn Silage - Ferrero, Francesco; Tabacco, Ernesto; Borreani, Giorgio (Frontiers in Microbiology, 2021)
Heterofermentative Lentilactobacillus hilgardii isolated from sugarcane silage, has recently been proposed as a silage inoculant to increase aerobic stability. Various conditions can influence the activity of LAB and their ability to alter silage quality (e.g. DM content and length of conservation). The aim of this study has been to evaluate the effect of L. hilgardii on the fermentation quality and aerobic stability of whole crop corn silage with different DM contents (from 26 to 45%), conserved for various conservation lengths (13 to 272 days). The silages were analyzed for their DM content, pH, fermentative profile, microbial count and aerobic stability. L. hilgardii showed a positive effect on improving the aerobic stability of silages, due its ability to produce acetic acid, and reduced the yeast count. The acetic acid content increased as the conservation period increased and decreased as the DM content increased. The yeast count was reduced during conservation in a DM dependent manner and the inoculation with LH determined a reduction in the count of 0.48 log cfu/g. The aerobic stability increased as the conservation period increased, and the treatment with LH on average increased the aerobic stability by 19 h. The results of this experiment suggest that higher aerobic stability could be achieved in corn silages by ensiling at medium or low DM contents, or by increasing the length of conservation if a higher DM content at ensiling is needed. The inoculation with LH helps to improve the aerobic stability of corn silages by reducing the yeast count.